Legal Certainty and Governance of Carbon Exchange Trading in Indonesia: An Analysis of the Implementation of Presidential Regulation Number 98 of 2021 - Rico Nur Ilham; Irada Sinta; Mangasi Sinurat; Muammar Khaddafi; Maulana Majied Sumatrani Saragih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Carbon exchange trading is an economic instrument developed to support greenhouse gas emission reduction and achieve sustainable development targets. In Indonesia, carbon trading is regulated by Presidential Regulation Number 98 of 2021 concerning the Management of Carbon Economic Value. This study aims to analyze the legal regulations for carbon exchange trading in Indonesia, the implementation of Presidential Regulation Number 98 of 2021 in achieving legal certainty, carbon trade governance, and the legal and institutional obstacles encountered in its implementation. The research method used is normative legal research with statutory, conceptual, and analytical approaches. Research data was obtained through a literature review sourced from laws and regulations, books, scientific journals, and other legal documents relevant to the research object. The results show that Presidential Regulation Number 98 of 2021 has provided a legal basis for the implementation of carbon trading through regulations regarding Carbon Economic Value, a national registration system, and mechanisms for measuring, reporting, and verifying emissions. However, its implementation still faces various obstacles, such as suboptimal regulatory harmonization, limited institutional coordination, unclear legal status of carbon units, and the need to strengthen the oversight system and legal protection for market players. Therefore, regulatory strengthening, institutional capacity building, and transparent and accountable governance are needed to create an effective, sustainable carbon market capable of supporting the achievement of Indonesia's greenhouse gas emission reduction targets.